PENINGKATAN KEMAMPUAN KEAKSARAAN DENGAN KARTU KATA BERGAMBAR MELALUI MEDIA KOMPUTER PADA KELOMPOK B DI RAUDHATUL ATHFAL BUNAYYA I TANJUNG SARI MEDAN SELAYANG TAHUN PELAJARAN 2013/2014 - Nuraisyah Anas (JURNAL TEMATIK, 2014)
This study aims to improve literacy skills with Word Picture Card Through Media Computers In Group B In RA Bunayya I Raudhatul Tanjung Sari Medan Selayang. This study is an action research using computer media , research carried out for 2 cycles each cycle consisting of 4 (four) meetings with a time of  2 x 30 minutes. The study subjects were all children of the class B Raudhatul RA Bunayya I Tanjung Sari Medan Selayang on Odd semester of school year 2013/2014, amounting to 15 people. Boys numbered 7 and 8 girls numbered. Collecting data using literacy tests and observation of the learning process. Observations made ​​on any action to obtain data about their activities that develop during the learning takes place. Data were analyzed using descriptive techniques. The results showed that children's literacy class B Raudhatul RA Bunayya I Selayang Medan Tanjung Sari has increased by 1.95 % after attending literacy learning with word cards illustrated through computer media. This increase can be seen from the results of literacy children acquire pre-action average by 56.67 there was an increase of 0.93 % literacy results, cycle I gained an average of 66.00 an increase literacy outcomes at 1.02 % and the second cycle gained an average of 76.13 an increase in results literacy by 1.95 %. literacy outcomes. Based on these results it can be concluded that the picture word cards via computer media can improve literacy skills of children and make learning more fun child. Thus the word cards illustrated through the medium of the computer can be used as an alternative for teachers in literacy learning serving.